Dichotomy of iterated means for nonlinear operators - Saburov, Mansoor (Springer Nature, 2018)
In this paper, we discuss a dichotomy of iterated means of nonlinear operators acting on a compact convex subset of a finite-dimensional real Banach space. As an application, we study the mean ergodicity of nonhomogeneous Markov chains.